Kebaron Village community empowerment through edutourism innovation - Niko Fediyanto; Indah Apriliana Sari Wulandari; Ida Agustini Saidi (Universitas Muhammadiyah Magelang, 2024)
Kebaron Village, recognized as a tourist destination boasting extensive rose-picking gardens, continues to encounter several challenges in managing its tourist area, resulting in suboptimal tourism potential and a limited number of visitors. These challenges encompass a dearth of directions to tourist sites and a lack of product diversity that appeals to visitors. This community service aims to bolster garden management and maximize the tourism potential of Kebaron Village by enhancing tourist allure through the improvement of facilities and the diversification of derivative products from red guava fruit. The methods employed include the installation of road signposts, creation and installation of Sapta Pesona points, as well as education on clean production and assistance in producing derivative products. The outcomes of this program entail an enhanced public understanding of clean production, along with improved skills in crafting derivative products from guava fruit, such as ice cream and leather. Additionally, the installation of road signposts and Sapta Pesona points has effectively heightened the accessibility and tourist allure of Kebaron Village.